Features of Statistical Accounting of Allergic Diseases in Children - Evidence from Moscow - Anita R. Denisova; Alexander B. Malahov; Alexandr N. Pampura; Elena A. Vishneva; Margarita A. Soloshenko; Nikoloz M. Gaboshvili; Leyla S. Namazova-Baranova (Union of pediatricians of Russia, 2023)
Background. The emergence of new functional capabilities of statistical accounting made it possible to conduct a comparative analysis of the morbidity of allergic pathologies according to the registers of allergists and pediatricians from the Unified Medical Information and Analytical System (UMIAS) of Moscow with data from the Form of Federal Statistical Observation No. 12 (FSO No. 12). The aim of the study is to investigate the potential of using UMIAS for assessing/monitoring the morbidity of allergic diseases, including bronchial asthma in children, using the example of several outpatient clinics (OPCs) in Moscow. Methods. A study of combined design has been carried out. The data of children of several OPCs in Moscow were analyzed - data from UMIAS (observation registers of pediatricians and allergist-immunologists) and from the reporting forms of the FSO No. 12. Results. For a comparative analysis of statistical data from UMIAS and FSO No. 12, we studied the information of 60,851 children under 18 years of age. It was revealed that out of 60,851 children: allergic rhinitis according to FSO No. 12 and UMIAS was established in 1001 and 1059 patients; atopic dermatitis - in 142 and 345; urticaria - in 363 and 33; angioedema - in 4 and 16, respectively; food allergy - in 233 children according (to FSO No. 12) and in none of the children (according to UMIAS). Out of 60,851 children, 619 children were diagnosed with bronchial asthma according to the annual report (FSO No. 12) and 537 according to the pediatrician's observation registers (UMIAS). At the same time, it was found that the diagnosis of bronchial asthma is not available as a separate nosology in the registry of an allergist-immunologist, and information about children with bronchial asthma is available to this specialist only when analyzing the uploaded information about children with other allergic diseases. Conclusion. A adequate sample ensured a high representativeness of the results obtained. The differences in the incidence rates of allergic diseases revealed by a comparative analysis of data from various sources - UMIAS and FSO No. 12 - indicate the need to improve both the system of statistical registration of incidence and the development of modern algorithms for early diagnosis and dynamic monitoring of children with allergies.